Physical, structural and antioxidant properties of brewer's spent grain protein films - Proaño Miniguano, Janina Lissette (2020)
The development of brewer's spent grain protein (BSG‐PC) films with potential active packaging properties was investigated. Films were prepared by casting protein dispersions at different pH values (2, 8, 11), plasticizers [polyethylene glycol (PEG) or glycerol] and levels (0–0.25 g g−1) of PEG. Mechanical, water‐barrier and solubility, optical, antioxidant (reducing power, ABTS•+ and lipidic radical scavenging), and antimicrobial properties of films were determined. Also, the structural characteristics of films were evaluated by attenuated total reflectance‐Fourier transform infrared spectroscopy.